2021
DOI: 10.3390/children8050362
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile/Adolescent Idiopatic Scoliosis and Rapid Palatal Expansion. A Pilot Study

Abstract: The question of whether orthodontic therapy by means of rapid palatal expansion (RPE) affects the spine during development is important in clinical practice. RPE is an expansive, fixed therapy conducted with heavy forces to separate the midpalatal suture at a rate of 0.2–0.5 mm/day. The aim of the study was to evaluate the influence of RPE on the curves of the spine of juvenile/adolescent idiopathic scoliosis patients. Eighteen patients under orthopedic supervision for juvenile/adolescent idiopathic scoliosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Based on the previous information, we could expect that not all spinal deformities are related to the stomatognathic system ( 50 ) but almost all IS seems to be related to this system ( 51 ). Our findings agree with the study by Piancino et al ( 51 ) as we observed that subjects with malocclusion present up to four times higher prevalence of scoliosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the previous information, we could expect that not all spinal deformities are related to the stomatognathic system ( 50 ) but almost all IS seems to be related to this system ( 51 ). Our findings agree with the study by Piancino et al ( 51 ) as we observed that subjects with malocclusion present up to four times higher prevalence of scoliosis.…”
Section: Discussionmentioning
confidence: 99%
“…Lippold et al concluded that early treatment by maxillary expansion therapy for lateral posterior crossbite did not produce any significant change in the spinal curves of the 31 children in the intervention group ( 50 ). On the other hand, Piancino et al assessed the effects of orthodontic therapy based on the rapid palatal expansion technique on juvenile/adolescent idiopathic scoliosis ( 51 ), observing that the Cobb angle worsened in participants during the treatment when compared with baseline and improved after removing the treatment compared with the curve angle during the treatment. Based on the previous information, we could expect that not all spinal deformities are related to the stomatognathic system ( 50 ) but almost all IS seems to be related to this system ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, even though the results are not directly translatable to humans, three animal studies 21–23 showed the role of induced malocclusion on the irreversible degeneration of the spine, manifesting as scoliotic curves. Moreover, the demonstration of possible associations of standard orthodontic therapies, such as rapid palatal expansion, on the worsening of scoliotic curves casts a shadow of concern that requires objective scientific clarification 24 . This disagreement might be due to the complexity of the system and to the great capacity for compensation in the three planes of space, that result in a variety of different responses and occlusal assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the demonstration of possible associations of standard orthodontic therapies, such as rapid palatal expansion, on the worsening of scoliotic curves casts a shadow of concern that requires objective scientific clarification. 24 This disagreement might be due to the complexity of the system and to the great capacity for compensation in the three planes of space, that result in a variety of different responses and occlusal assessment.…”
mentioning
confidence: 99%